2021
DOI: 10.1098/rsos.201205
|View full text |Cite
|
Sign up to set email alerts
|

Abstract concepts in interaction: the need of others when guessing abstract concepts smooths dyadic motor interactions

Abstract: concepts (ACs, e.g. ‘justice’) are more complex compared with concrete concepts (CCs) (e.g. ‘table’). Indeed, they do not possess a single object as a referent, they assemble quite heterogeneous members and they are more detached from exteroceptive and more grounded in interoceptive experience. Recent views have hypothesized that interpersonal communication is particularly crucial to acquire and use ACs. The current study investigates the reliance of ACs/CCs representation on interpersonal behaviour. We asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…In one block of trials, they were told that the avatar embodied and was guided by one of the experimenters, and in the second block, they were told that the avatar embodied and was guided by the other experimenter; they were also informed that another guessing session would follow. Participants' movements were more synchronous with those of the avatar embodying the experimenter who offered suggestions regarding abstract concepts (Fini et al, 2021). Separate analyses showed that they felt they needed an experimenter's Possible mechanisms underlying how we process words expressing abstract concepts.…”
Section: Concepts and Joint Action: Novel Research Avenuesmentioning
confidence: 95%
“…In one block of trials, they were told that the avatar embodied and was guided by one of the experimenters, and in the second block, they were told that the avatar embodied and was guided by the other experimenter; they were also informed that another guessing session would follow. Participants' movements were more synchronous with those of the avatar embodying the experimenter who offered suggestions regarding abstract concepts (Fini et al, 2021). Separate analyses showed that they felt they needed an experimenter's Possible mechanisms underlying how we process words expressing abstract concepts.…”
Section: Concepts and Joint Action: Novel Research Avenuesmentioning
confidence: 95%
“…In the second study implemented through kinematics techniques [189], participants were asked to predict the actions of an avatar on the screen in order to plan their own actions towards a bottle-shaped object (joint action task) (e.g., [190,191]). The participants could freely choose how to grasp the object (they could use either the upper part with a precision grip or the lower part with a power grip), but they were asked to perform either imitative or complementary actions with respect to the avatar's actions.…”
Section: Grounding Abstract Concepts In Social Interactionsmentioning
confidence: 99%
“…We have called social metacognition (Borghi et al, 2018 ) the process occurring when we fail to find responses in ourselves and resort to others (Shea, 2018 ). Consistent evidence shows that participants performing an image-word guessing task tend to ask more for advice from others with abstract compared to concrete words; when performing a subsequent joint action task they show more inter-individual synchrony (Fini et al, 2021a ). Furthermore, much evidence showed higher activation of the mouth motor system during abstract than concrete concepts acquisition and processing (review: Mazzuca et al, 2021 ; see also Ghio et al, 2013 ; Dreyer and Pulvermüller, 2018 ; Fini et al, 2021b ; Reggin et al, 2021 ).…”
Section: Abstract Concepts and Beliefmentioning
confidence: 95%